ΜRate: An online dose rate calculator for trapped charge dating. (10th October 2022) - Tudyka, Konrad; Koruszowic, Michał; Osadnik, Rafał; Adamiec, Grzegorz; Moska, Piotr; Szymak, Agnieszka; Bluszcz, Andrzej; Zhang, Junjie; Kolb, Thomas; Poręba, Grzegorz
Abstract: In this work, we present a new online service for dose rate calculations in trapped charge dating called "μRate". The app provides a graphical user interface, convenient cloud storage of data, and the ability to exchange data between users. The data records are organised into projects, which can be easily recalculated with modified parameters. Calculations can be carried out for a wide variety of input data originating from different instruments. Radionuclide concentrations can be supplied in several formats and units. The calculations' results can be easily exported. The tool has been created specifically to maximise the flexibility of use and provide a stringent uncertainty estimation using the Monte Carlo method. In addition, μRate can perform a Sobol sensitivity analysis that can help assess the significance and risks associated with each parameter used in calculations. In addition, the app allows for temporal variability in cosmic radiation intensity, which may be of significance in low dose rate samples. The app's results are compared with other dose rate calculation methods, namely Dose4Win, DRAC, and dose rate R scripts, all used in the Leibniz Institute for Applied Geophysics, indicating good agreement with other calculation methods.